An Analysis of the COVID-19 Impact on Business and Social Performance of Islamic Micro-Financial Institutions - Riduwan Riduwan; Rofiul Wahyudi; Dwi Santosa Pambudi Pambudi; Ahmad Arif Rifan (Universitas Ahmad Dahlan, 2022)
Islamic micro-financial institutions (LKMS) provide services for micro businesses in the form of deposits, financing, and social assistance as the main activities. The COVID-19 pandemic engenders an adverse impact, breeding members’ inabilities to measure up to their duties. The inabilities are regretted as LKMS should have also been able to assist its members in sustaining as a form of social responsibility. The research aims to prove paradoxes in business and social performance. We applied a descriptive quantitative approach to a secondary data analysis of business and social performance reports during the COVID-19 pandemic until 2021. The research population covered 154 members of the Islamic cooperative parent, and the samples were 51 LKMS in the Islamic cooperative center. Conclusions were drawn from data analysis using stakeholder and stewardship theories. The results demonstrated that the COVID-19 pandemic incurred negative impacts, i.e., a decreased business performance of LKMS of 8.4% on average for two years. Meanwhile, another finding exhibited an increase in social performance by 27%. Based on the data, we could argue that a decrease in LKMS business performance bred an increase in social performance.